Pengaruh Rekrutmen dan Promosi Jabatan terhadap Kinerja Karyawan pada PT. Jambi Wood Industri - Akhmadi Akhmadi; Jasasila Jasasila (Universitas Batanghari Jambi, 2019)
One of the activities in HR management is the recruitment and promotion of positions. Recruitment is a process of gathering a number of applicants who have qualifications in accordance with what is needed by the company, to be employed company (Malthis, 2001). The benefits of recruitment is to have the function of